Diálogos entre o currículo da pedagogia Waldorf e a formação integral - Carvalho, Laura Diniz Rocha Campolin de (2022)
This research arose from the desire to deepen and share ideas that seek an education that aims not only at the cognitive/intellectual formation of the student, but that contemplates in its curriculum, in addition to this formation, the affective, emotional, social formation, among others, that is, their comprehensive training. In this way, we consider relevant to reflect on curricula that aim to build a teaching that seeks to meet the needs of each student, providing conditions for an integral procedural development, aiming to form a human being prepared to face the challenges of life. The object of this study was Pedagogy, as it contemplates in its curriculum knowing the human being in its physical, mental (psycho-emotional) and spiritual (individuality) aspects, that is, as a being in its entirety. As a general objective, we seek to understand the elements present in the curriculum based on the assumptions of Waldorf Pedagogy that provide the integral development of the human being, contemplating it in its social, physical, psychic-emotional aspects, considering individuality and committed to the integral formation of the students. An attempt was made to identify the curriculum provided to students from the 5th to the 8th grade inserted in Waldorf Pedagogy; to characterize the integral formation in the perspective of the Waldorf curriculum and to analyze, from interviews with 9th grade students, graduates, and teachers of a school in Cuiabá, which works from the Waldorf assumptions, how the Human Formation process based on this curriculum takes place. The option was for a qualitative approach research, with semistructured interviews, using Stephen Ball's Policy Cycle approach for data analysis. From the analysis of the interviews, it was possible to consider that Waldorf Pedagogy can offer significant contributions to the integral formation of young people, as it is effective in the formation of free, committed, and prepared human beings to face the challenges of life.